Points of Time, Points in Time, Points in Space. Agostino Di Scipio's Early Works (1987–2000). - Zattra, Laura (Contemporary Music Review, 2014)
This paper bears on Agostino Di Scipio's work from the years 1987–2000. Early computer-generated pieces likePunti di tempo(1987) andEstensioni(1988) seem to reflect a kind of double artistic individuality. In the first piece, the musical structure is fragmented and the sound micro-structure is split in random particles. In the second (the only piece Di Scipio made with digital additive synthesis methods) both sound and the overall musical structure are worked out in a deeply deterministic way. This dualism returns frequently in Di Scipio's early career: the qualitative exploration of infinitesimal sonic units with related concepts of ‘granular’ sound, and a formalized approach to the musical macrostructure (algorithmic composition) seem to complement each other. In the winter of 1994–1995, Di Scipio started working with real-time signal processing and live electronics. He started investigating space-related phenomena, and to address himself to composing the instruments (i.e. designing the overall performance infrastructure) as a task different from composing for existing instruments, whether these are usual musical instruments or computational tools. In the new orientation, a more comprehensive view of the ‘performance ecosystem’ turned out to be crucial, and it led to important later developments (theAudible Ecosystemicsseries of live-electronics works). The present paper investigates these early stages in Di Scipio's career. It builds on a variety of sources and archival documents, and emphasizes that the composer's early efforts did not follow a linear path but rather raised issues and implications spreading out fanwise from one specific conceptual knot: the one concerning ‘emergence’ (‘sonological’ and ‘formal’ emergence).